1994
DOI: 10.2307/2160836
|View full text |Cite
|
Sign up to set email alerts
|

Schur's Double Centralizer Theorem for Triangular Hopf Algebras

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org. This content downloaded from 128.235.251.160 on Mon, ABSTRACT. Let (H, R) be a triangular Hopf algebra and let V be a finitedimensional representation of H. Following Manin we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Recall from [2] that a quasitriangular Hopf algebra is a pair (H, R) where H = (H, µ, η, ∆, ε, S) is a Hopf algebra endowed with an invertible element R = R (1) ⊗ R (2) ∈ H ⊗ H (called a universal R-matrix), satisfying the following conditions:…”
Section: Quasitriangular Hopf Algebramentioning
confidence: 99%
See 1 more Smart Citation
“…Recall from [2] that a quasitriangular Hopf algebra is a pair (H, R) where H = (H, µ, η, ∆, ε, S) is a Hopf algebra endowed with an invertible element R = R (1) ⊗ R (2) ∈ H ⊗ H (called a universal R-matrix), satisfying the following conditions:…”
Section: Quasitriangular Hopf Algebramentioning
confidence: 99%
“…ad 2 x (R (2) · α(m))α 2 ([R (1) · l, y]) = 0, (2.4) for all y ∈ I, l ∈ [L, L], m ∈ L. We now consider the following two cases: …”
Section: Substituting (22) and (23) Into (21) We Obtainmentioning
confidence: 99%
“…For a quasitriangular Hopf algebra H R [3], it is easy to see that the category H is a Yetter-Drinfeld category under the comodule coaction m = R 2 ⊗ R 1 · m for all m ∈ M ∈ H . In particular, if H is triangular, then the condition that R is convolution invertible means that the category H is braided symmetric.…”
Section: )mentioning
confidence: 99%
“…Furthermore, in the framework of a symmetric monoidal category, Schauenburg [14] showed that the category of Hopf bimodules is a braided monoidal category by constructing a braided monoidal category equivalence between the category of Hopf bimodules and the category of Yetter-Drinfel'd modules. On the other hand, the study of braided Lie algebras has been an interesting topic (see Bahturin et al [1], Cohen et al [6], Majid [10,11] and Wang [16,18,20]). For example, Wang [18] studied the braided Lie structures of an algebra A in the braided monoidal category of Yetter-Drinfel'd modules (see also Wang [21]).…”
Section: Introductionmentioning
confidence: 99%